¿Quién es el antropólogo o antropóloga? - Bizeul, Daniel (Pontificia Universidad Católica del Perú, 2025)
The anthropologist as a person often remains a blind spot. Yet it is the fit, more or less favorable or unfortunate, between a specific social context and a particular anthropologist that partly shapes the course and outcome of fieldwork. Hence the importance of mentioning the anthropologist’s biographical events and experiences, as well as his or her physical and relational characteristics, insofar as they have an impact throughout the work. Such information helps readers better assess the quality of the research. However, this form of self-analysis remains an uncertain exercise, without protocol or model. Drawing on the example of an immersive fieldwork I carried out between 1996 and 1999 within the National Front, a French far-right political party, I show how the research was facilitated by my Catholic and right-wing upbringing, and complicated by my intimate life with two men, one of whom was Black.

La faceta personal del antropólogo sigue siendo a menudo un punto ciego en el trabajo de investigación. Sin embargo, es la adecuación más o menos favorable entre un antropólogo singular y un contexto social definido lo que determina en parte el curso de una investigación y la calidad de los resultados. De ahí la importancia, habitual en Francia, de mencionar los acontecimientos biográficos y las experiencias propias del antropólogo o la antropóloga. Esto ayuda al lector a juzgar la calidad de la investigación y la precisión del análisis. Esta forma de autoanálisis sigue siendo un ejercicio incierto, sin protocolo ni modelo. A partir del ejemplo de una investigación de inmersión realizada entre 1996 y 1999 sobre el Frente Nacional, partido francés de extrema derecha, muestro cómo la investigación se vio facilitada por mi educación católica y de derechas, y complicada por mi vida amorosa con dos hombres, uno de ellos moreno.
Who is the Anthropologist?
Keywords: Fieldwork account; Truth; Ethnographic reflexivity; Self-analysis; Far-right; Homosexuality; France; Relato etnográfico; Verdad; Autoanálisis; Extrema derecha; Homosexualidad; Francia; https://purl.org/pe-repo/ocde/ford#5.04.03